Effects on confocal laser endomicroscopy image quality by different acriflavine concentrations - Li, Chang-Qing (Landes Bioscience, 2011)
BACKGROUND: Acriflavine is one of the commonly used staining agents in confocal laser endomicroscopy (CLE), a newly developed technique allows for real time histological observation of gastrointestinal mucosa, but the concentration is not unified. This study aimed to evaluate the effects of acriflavine with different concentrations on the CLE image quality and to find a sound concentration in clinical practice. METHODS: Twenty four consecutive patients who underwent upper gastrointestinal CLE were enrolled into this study. The patients randomly accepted acriflavine in four different concentrations which were the conventional 0.05% and 3 lower ones respectively: 0.02%, 0.01% and 0.005% spraying onto the same focal antrum mucosa during CLE procedures. Differences of Image quality were demonstrated by an objective score system. RESULTS: There was no significant difference about image quality among acriflavine concentrations: 0.05%, 0.02% and 0.01%, but 0.005% decreased image quality significantly (P=0.012). And 0.005% was also the only one which decreased general assessment significantly (P=0.01). For the 3 diagnostic value assessment indices, there was no significant difference about nonspecific and even staining, while 0.02% showed significant better polar staining (P=0.03). CONCLUSIONS: Acriflavine concentration 0.02% is the best one applied in CLE with the best nuclei staining ability and preserved image quality.